Chorioretinal scars and visual deprivation are common in children with cochlear implants after congenital cytomegalovirus infection. (27th March 2015) - Teär Fahnehjelm, Kristina; Olsson, Monica; Fahnehjelm, Cecilia; Lewensohn‐Fuchs, Ilona; Karltorp, Eva
Abstract Aim The aim of this study was to compare visual function and ocular characteristics in children with cochlear implants, due to severe hearing impairment caused by the congenital cytomegalovirus (CMV) infection, with control children fitted with cochlear implants due to connexin 26 mutations (Cx26), a genetic cause of hearing impairment. Methods We carried out ophthalmological assessments, including visual acuity, ocular alignment, Ocular Motor Score, biomicroscopy and fundus photography, on 26 children with congenital CMV (median age 8.3 years, range 1.4–16.7) and 13 Cx26 controls (median age 5.6 years, range 1.7–12.5). Results We found unilateral chorioretinal macular scars that reduced best‐corrected visual acuity ≤0.3 in five (19%) of the children with congenital CMV, but in none of the children with Cx26 (p = 0.15). Ocular motility problems were more common among children with congenital CMV, but the difference was not significant (p = 0.20). The vestibulo‐ocular reflex was more frequently pathological in children with congenital CMV (p = 0.011). Conclusion Ocular complications with central chorioretinal scars and ocular motility disturbances were common in children treated with cochlear implants due to severe hearing impairment caused by the congenital CMV infection. Ophthalmological assessments are advisable in such children for early identification, intervention and follow‐up.